Ubiquitination of the G1 cyclin Cln2p by a Cdc34p-dependent pathway. - Deshaies, R J (EMBO J, 1995)
Recombinant G1 cyclin Cln2p can bind to and stimulate the protein kinase activity of p34CDC28 (Cdc28p) in an extract derived from cyclin-depleted and G1-arrested Saccharomyces cerevisiae cells. Upon activating Cdc28p, Cln2p is extensively phosphorylated and conjugated with multiubiquitin chains. Ubiquitination of Cln2p in vitro requires the Cdc34p ubiquitin-conjugating enzyme, Cdc28p, protein phosphorylation and unidentified factors in yeast extract. Ubiquitination of Cln2p by Cdc34p contributes to the instability of Cln2p in vivo, as the rate of Cln2p degradation is reduced in cdc34ts cells. These results provide a molecular framework for G1 cyclin instability and suggest that a multicomponent, regulated pathway specifies the selective ubiquitination of G1 cyclins. IMAGES: